2006
DOI: 10.1038/sj.jes.7500489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hypothesis that Balkan endemic nephropathy is caused by drinking water exposure to contaminants leaching from Pliocene coal deposits

Abstract: Balkan endemic nephropathy (BEN) is a kidney disease that has been reported in only certain rural villages in Serbia, Bulgaria, Romania, Croatia and Bosnia. The cause of BEN remains a mystery, but researchers seem to agree that exposure to one or more environmental agents is at least partially responsible. The Pliocene lignite hypothesis suggests the disease is due to long-term exposure to polycyclic aromatic hydrocarbons (PAHs) or other toxic organic compounds that have leached into drinking water supplies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
1
36
0
1
Order By: Relevance
“…The Pliocene lignite hypothesis posits that BEN is caused by long-term exposure to low concentrations of toxic organic compounds leaching into drinking water, that is used almost exclusively by the population, via groundwater from Pliocene lignites found in the vicinity of endemic settlements. 16,24,27,28 Many studies have been conducted to test the role of the Pliocene lignite hypothesis in the etiology of BEN, [27][28][29][30][31][32][33][34][35][36][37][38][39] and many characteristics of the disease have been shown to be consistent with the hypothesis. For example, of immigrants who settled into endemic areas, only after a minimum of y20 years were they likely to develop the disease, suggesting low dose exposure to, e.g., a fixed environmental factor.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The Pliocene lignite hypothesis posits that BEN is caused by long-term exposure to low concentrations of toxic organic compounds leaching into drinking water, that is used almost exclusively by the population, via groundwater from Pliocene lignites found in the vicinity of endemic settlements. 16,24,27,28 Many studies have been conducted to test the role of the Pliocene lignite hypothesis in the etiology of BEN, [27][28][29][30][31][32][33][34][35][36][37][38][39] and many characteristics of the disease have been shown to be consistent with the hypothesis. For example, of immigrants who settled into endemic areas, only after a minimum of y20 years were they likely to develop the disease, suggesting low dose exposure to, e.g., a fixed environmental factor.…”
Section: Introductionmentioning
confidence: 92%
“…However, many limitations of the hypothesis have been noted in the literature. 16,24,26,28,35,36,[40][41][42][43][44][45][46][47] In addition, criticisms of a number of previous studies that were conducted to test the hypothesis have been raised, casting doubt on its validity. For example, evaluations of the research that addressed the Pliocene lignite hypothesis concluded that the primary evidence in support of it is merely the spatial association between lignite deposits and BEN endemic villages, 41 but that the spatial correlation is nothing ''more than fortuitous.''…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, these CKDue epidemics are localised in the dry zones of agricultural societies, where the landscape is flat and the ground conditions are harsh, with little rain and prolonged dry periods and drought. Examples of somewhat similar CKDu conditions reported in other countries include Uddanam, in the agricultural belt of Andhra Pradesh [7]; unusual nephropathy, in China [8] and Nicaragua [9]; and Balkan endemic nephropathy, which affects rural villages in Serbia, Bulgaria, Romania, Croatia, and Bosnia [10,11].…”
Section: Uniqueness Of the Ckd-mfomentioning
confidence: 98%
“…In many of these regions, CKDue has been reported for more than four decades without identification of any specific causative factor(s). Although ground conditions and the histopathologic features of these CKDs are somewhat similar, the postulated causes are different amongst these countries [8,10,15,16]. While some have been attributed to natural (e.g.…”
Section: Uniqueness Of the Ckd-mfomentioning
confidence: 99%
See 1 more Smart Citation